(2z+3)(6+z)=0

Simple and best practice solution for (2z+3)(6+z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2z+3)(6+z)=0 equation:


Simplifying
(2z + 3)(6 + z) = 0

Reorder the terms:
(3 + 2z)(6 + z) = 0

Multiply (3 + 2z) * (6 + z)
(3(6 + z) + 2z * (6 + z)) = 0
((6 * 3 + z * 3) + 2z * (6 + z)) = 0
((18 + 3z) + 2z * (6 + z)) = 0
(18 + 3z + (6 * 2z + z * 2z)) = 0
(18 + 3z + (12z + 2z2)) = 0

Combine like terms: 3z + 12z = 15z
(18 + 15z + 2z2) = 0

Solving
18 + 15z + 2z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(6 + z)(3 + 2z) = 0

Subproblem 1

Set the factor '(6 + z)' equal to zero and attempt to solve: Simplifying 6 + z = 0 Solving 6 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + z = 0 + -6 z = 0 + -6 Combine like terms: 0 + -6 = -6 z = -6 Simplifying z = -6

Subproblem 2

Set the factor '(3 + 2z)' equal to zero and attempt to solve: Simplifying 3 + 2z = 0 Solving 3 + 2z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2z = 0 + -3 2z = 0 + -3 Combine like terms: 0 + -3 = -3 2z = -3 Divide each side by '2'. z = -1.5 Simplifying z = -1.5

Solution

z = {-6, -1.5}

See similar equations:

| (x+4)+x=340 | | 3/4-3/5x=7/20 | | m-8m+8m-1= | | 5(x-4)=3(x-12) | | 120/82=7/10 | | -(8y+4z+7)= | | -1/2=c-8/9 | | 0=116t^2+64t-60 | | 80=2W+L | | 5/12=5/6y | | 8N-3N=35 | | 2y-12=y+6 | | 4(x-4)=2x+18 | | AX+5=17 | | x^2=12x-4 | | 7+x=1000998 | | 72=-16t+64t+12 | | 7x+8=32 | | -(1/6)(x-18)+(1/2)(x+2)=x+16 | | 8x^3+5xy+8y^2+5y=0 | | -(7y+1)-(-6y-7)=-1 | | 8m^3+5mn+8m^2+5n=0 | | 8x-9=2x-6 | | 8m^3+216=0 | | 3+13z-1=8z+37-2z | | 7+2z-5=9z+4-6z | | 2/3y=2 | | 4p+6p=80 | | Y/7=-27 | | 4m+n+m= | | 2n+6n=40 | | 12x^3-36x=0 |

Equations solver categories